Simplifying glycan monitoring of complex antigens such as the SARS-CoV-2 spike to accelerate vaccine development - Janelle Sauvageau; Izel Koyuturk; Frank St. Michael; Denis Brochu; Marie-France Goneau; Ian Schoenhofen; Sylvie Perret; Alexandra Star; Anna Robotham; Arsalan Haqqani; John Kelly; Michel Gilbert; et al. (Communications Chemistry, 2023)
Abstract Glycosylation is a key quality attribute that must be closely monitored for protein therapeutics. Established assays such as HILIC-Fld of released glycans and LC-MS of glycopeptides work well for glycoproteins with a few glycosylation sites but are less amenable for those with multiple glycosylation sites, resulting in complex datasets that are time consuming to generate and difficult to analyze. As part of efforts to improve preparedness for future pandemics, researchers are currently assessing where time can be saved in the vaccine development and production process. In this context, we evaluated if neutral and acidic monosaccharides analysis via HPAEC-PAD could be used as a rapid and robust alternative to LC-MS and HILIC-Fld for monitoring glycosylation between protein production batches. Using glycoengineered spike proteins we show that the HPAEC-PAD monosaccharide assays could quickly and reproducibly detect both major and minor glycosylation differences between batches. Moreover, the monosaccharide results aligned well with those obtained by HILIC-Fld and LC-MS.